Answers

2015-04-23T03:17:34+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
P(x)  =  x⁴  - 6 x³ + 16 x² - 25 x + 10
         = (x²)² - x² * 6 x + 16 * x²  - 25 x + 10

Instead of long division, i am doing as follows:
       divisor:  x²  - 2 x + k 
      so substitute  x² - 2x + k = 0    or    x² = 2 x - k  in  P(x)

 remainder  =    (2 x - k)²  - 6 x ( 2x - k )  + 16 (2x - k) - 25 x + 10
               =  4x² - 4 k x + k² - 12 x² + 6 x k + 32 x - 16 k  - 25 x + 10
             =  - 8 x² + 2 k x + 7 x + k² - 16 k + 10
            =   - 8 (2 x - k) + 2  k x + 7 x + k² - 16 k + 10
           =  (- 9  + 2 k ) * x +  k² - 8 k + 10

   as the remainder is x + a  .  compare with the above expression:
           2 k - 9 = 1      and  so  k = 5
       10 - 8 k + k² = a      =>    a = - 5

=============================

long division

      x² - 2x + k  )  x⁴ - 6 x³ + 16 x² - 25 x + 10  (  x²  - 4 x  + (8-k)
                           x⁴  - 2 x³  + k x²
                     ======================
                              - 4 x³ + (16-k) x² - 25 x
                              - 4 x³  + 8 x² - 4 k x
               ================================
                                       (8-k) x² + (4 k - 25) x  + 10
                                       8-k) x²   - 2 (8-k) x   + k (8-k)
                    ===============================
                                    (2 k  - 9) x + 10 - 8 k + k²

 we are given that  reminder is  x + a
      =>  2 k - 9 = 1      hence,    k = 5
     =>     a = 10 - 8 k + k² = - 5 
 


2 3 2
How can you take 2k - 9 =
the above answer is correct and right.
what is the answer you have got , please inform
although the answer is same the method is un understandable
can you tell me how you can substitute 2k - 9 = 1